Comparative genomics and transcriptomics reveal differences in effector complement and expression between races of Fusarium oxysporum f.sp. lactucae - Bates, Helen J.; Pike, Jamie; Price, R. Jordan; Jenkins, Sascha; Connell, John; Legg, Andrew; Armitage, Andrew; Harrison, Richard J.; Clarkson, John P. (Frontiers in Plant Science, 2024)
This study presents the first genome and transcriptome analyses for Fusarium oxysporum f. sp. lactucae (Fola) which causes Fusarium wilt disease of lettuce. Long-read genome sequencing of three race 1 (Fola1) and three race 4 (Fola4) isolates revealed key differences in putative effector complement between races and with other F. oxysporum ff. spp. following mimp-based bioinformatic analyses. Notably, homologues of Secreted in Xylem (SIX) genes, also present in many other F. oxysporum ff. spp, were identified in Fola, with both SIX9 and SIX14 (multiple copies with sequence variants) present in both Fola1 and Fola4. All Fola4 isolates also contained an additional single copy of SIX8. RNAseq of lettuce following infection with Fola1 and Fola4 isolates identified highly expressed effectors, some of which were homologues of those reported in other F. oxysporum ff. spp. including several in F. oxysporum f. sp. apii. Although SIX8, SIX9 and SIX14 were all highly expressed in Fola4, of the two SIX genes present in Fola1, only SIX9 was expressed as further analysis revealed that SIX14 gene copies were disrupted by insertion of a transposable element. Two variants of Fola4 were also identified based on different genome and effector-based analyses. This included two different SIX8 sequence variants which were divergently transcribed from a shared promoter with either PSE1 or PSL1 respectively. In addition, there was evidence of two independent instances of HCT in the different Fola4 variants. The involvement of helitrons in Fola genome rearrangement and gene expression is discussed.